Factores socioculturales y actitud hacia la sexualidad en estudiantes del nivel secundaria de la Institución Educativa N° 60024, San Juan Bautista 2021 - Tenazoa Vasquez, Jerson (2025)
The objective was to determine the relationship between sociocultural factors and attitude towards sexuality in high school students of educational institution No. 60024 San Juan Bautista, district of San Juan Bautista - 2021. Sociocultural factors are defined as the influences of society and culture in people's behavior, attitudes and beliefs, affecting how they interact, relate to their environment and make decisions (Orther, 2020). Attitude toward sexuality is conceptualized as the beliefs, values, and behaviors related to sexuality (Butler, 2000). The study was descriptive, with a non-experimental design and correlational approach, collecting data at a single moment. The population consisted of 173 high school students distributed in two shifts: morning (section “A” with 47 students and “B” with 49) and afternoon (section “C” with 37 and “D” with 40). The data were processed with SPSS version 26, organized in tables and represented graphically. To evaluate the relationship between sociocultural factors and attitude towards sexuality, non-parametric tests were used, such as Spearman's rho, which uses Student's t with n-2 degrees of freedom for contrast (Table No. 6). The results indicate that sociocultural factors are related to the attitude towards sexuality in high school students of educational institution No. 60024 San Juan Bautista, district of San Juan Bautista - 2021.